Sarcopenia e hepatite c crônica: avaliação dos fatores relacionados ao vírus, ao hospedeiro e ao estilo de vida - Thais Pontello de Vries (2021)
Background: Sarcopenia is a remarkable finding in patients with chronic hepatitis C (CHC). However, the biological mechanisms behind the skeletal muscle loss have not been completely clarified. Objective: To evaluate independent associations between sarcopenia and its components, appendicular skeletal mass index (ASMI) and handgrip strength (HGS) and host-, disease-, nutritional- and virus-related factors and to appraise association between bioelectrical impedance analysis (BIA)-derived phase angle (PhA) values and sarcopenia in patients with chronic hepatitis C. Methods: Ninety outpatients with CHC (mean age, 49.9 + 11.3yrs.; 73.3% males; 67.8% non-cirrhotic and 32.2% with compensated cirrhosis) underwent scanning of ASM and bone mass by dual-energy X-ray absorptiometry. Sarcopenia was defined as the presence of both low ASMI and low HGS according to the European Working Group on Sarcopenia in Older People criteria. Osteopenia and osteoporosis were defined according to the World Health Organization criteria. The International Physical Activity Questionnaire was used to determine the physical activity level. Associations were investigated by logistic and linear regression models. Results: Sarcopenia, low SMI and low HGS were found in (5.6%), 12.2% and 17.8% patients, respectively. In the multivariate analysis, low ASMI and sarcopenia were positively associated with low bone mass and inversely associated with PhA. Low HGS was inversely associated with PhA. Considering the PhA as dependent variable, age, male sex, diabetes mellitus and sarcopenia were independently associated with this BIA-derived measurement. Conclusion PhA may be considered an useful indicator of sarcopenia and its components in patients with CHC. This BIA-derived measurement has been recognized as marker of overall muscle quality.